PERFORMANCE ANALYSIS OF THE PROTOCOL AND LEADERSHIP COMMUNICATIONS DIVISION IN SUPPORTING LEADERSHIP ACTIVITIES IN METRO CITY - Rendini Elenza; Malik (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the performance analysis of the Protocol and Communications Section of the Leadership in Supporting Leadership Activities in Metro City. All data was obtained directly from informants in the field using interviews and document studies. The results of the study indicate that employee performance has generally been quite good, but not yet fully optimal. (a) The quantity of work, the high task load, has not been fully balanced by the availability of adequate resources. (b) The quality of work indicates the need to improve the consistency of task implementation. (c) Timeliness remains an obstacle influenced by changes in the leadership agenda. (d) Initiative and responsibility: some employees have not yet fully demonstrated a proactive attitude. (e) Leadership cooperation has not been optimal due to ineffective coordination and communication. (f) Work attitudes and behaviors: Strengthening employee discipline, work ethics, and professionalism is still needed to support the smooth running of leadership activities.